THE RELATIONSHIP BETWEEN BODY MASS INDEX (BMI), ALBUMIN LEVELS, MEAN ARTERIAL PRESSURE (MAP), AND FOOD INTAKE ON THE INCIDENCE OF PREECLAMPSIA: A PROSPECTIVE COHORT STUDY - Hirfa Turrahmi; Tria Astika Endah Permatasari; Heri Rosyati; Elli Hidayati (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Preeclampsia and eclampsia have the greatest impact on the morbidity and mortality of pregnant women and newborns. Management of patients with manifestations of preeclampsia requires a well-formulated plan that takes into account maternal risk factors, clinical, laboratory, and imaging (X-ray) findings, and time of onset gestational age, and delivery. The purpose of this study was to determine the relationship between body mass index (BMI), albumin levels, mean arterial pressure (MAP), and food intake on the incidence of preeclampsia. This prospective cohort study was conducted at the Community Health Centers working area of ​​Central Jakarta from October 2021 to May 2022. A sample of 167 pregnant women was selected using consecutive sampling with inclusion criteria of 13-16 weeks gestation and was willing to participate in the research program. Samples who had communication disorders were on routine medication, and had a history of other diseases, except for hypertension, were excluded from the study. Data processing uses the SPSS 22.0 program with independent t-test and chi-square test analysis. The results showed that 8.4% of pregnant women with preeclampsia were positive, there was a significant relationship between age (p = 0.042; RR = 2.99; 95% CI: 1.00-9.16); spacing of pregnancies (p= 0.008; RR= 3.97; 95% CI: 1.46-10.78); maternal history of hypertension (p= 0.002; RR= 5.18; 95% CI: 1.98-13.59); BMI in early pregnancy (p= 0.001; RR= 6.02; 95% CI: 1.98-18.28); albumin level (p= 0.001; RR= 13.48; 95% CI: 1.80-100.69); MAP (p< 0.001; RR= 10.93; 95%CI: 4.47-26.70); animal protein intake (p= 0.024; RR= 3.13; 95%CI: 1.10-8.91); and vegetable intake (p= 0.038; RR= 2.79; 95%CI: 1.02-7.64) with preeclampsia. Preventing the occurrence of preeclampsia can be done by early examination of albumin levels and maintaining food intake.